Institutional Ownership Activism, Market Performance, and Financial Crisis: Evidence From an Emerging Market - Panda, B. D. (Animo Repository, 2018)
This paper investigates the trading and investment behavior of the institutional investors in the Indian capital market post-financial crisis and their effect on the market performance. The study is based on the panel data sets drawn from the NIFTY 500 companies for eight years from FY 2008–09 to FY 2015–16, employing panel data econometric models (fixed effect and random effect) analysis. The results suggest that foreign institutional investors (FII) are having the edge over the domestic institutional investors (DII) in the Indian market. FIIs enhance the market performance, whereas DIIs dampen the market performance. Subsequently, we find that equity investment from banks and insurance companies have a detrimental effect, while mutual fund investment has no significant impact on the market performance of the Indian firms. These results imply that FIIs are better-informed players and follow the positive feedback trading behavior. On the other hand, DIIs, banks, and insurance companies are contrary investors and act as negative feedback traders.